2020
DOI: 10.2478/raon-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Combining radiotherapy and immunotherapy in definitive treatment of head and neck squamous cell carcinoma: review of current clinical trials

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSCC) presents as locally advanced disease in a majority of patients and is prone to relapse despite aggressive treatment. Since immune checkpoint inhibitors (ICI) have shown clinically significant efficacy in patients with recurrent/metastatic HNSCC (R/M HNSCC), a plethora of trials are investigating their role in earlier stages of disease. At the same time, preclinical data showed the synergistic role of concurrently administered radiotherapy and ICIs (immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 139 publications
0
11
0
2
Order By: Relevance
“…Indeed, immune checkpoint inhibitors have become a standard in the treatment of recurrent or metastatic HNSCC and are now being tested prospectively in the locally-advanced setting. Through immunogenic cancer cell death and effect on the tumour microenvironment and vasculature, RT may enhance the effect of immune checkpoints inhibitors 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immune checkpoint inhibitors have become a standard in the treatment of recurrent or metastatic HNSCC and are now being tested prospectively in the locally-advanced setting. Through immunogenic cancer cell death and effect on the tumour microenvironment and vasculature, RT may enhance the effect of immune checkpoints inhibitors 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The same can be said about the GORTEC 2015-01 PembroRad trial, which failed to improve locoregional control over SOC using pembrolizumab plus radiation (125). However, these are just two of the many ongoing trials involving LA HNSCC (118)(119)(120)(121)(122)(123). More importantly, some recent trials, albeit fewer in comparison, are now evaluating ICIs combinations specifically in LA, HPV + OPSCC with and without reductions in the dosage of radiation (Table 1).…”
Section: Targeting the Tumor Microenvironment Of Hpv +-Hnsccmentioning
confidence: 98%
“…Harnessing the positive effects of radio-and chemotherapy can therefore increase the proportion of responders and amplitude of response to ICIs and help with de-escalation endeavors. To that end, a number of clinical trials have incorporated ICIs in combination with radiation, chemotherapy or experimental targeted therapies for evaluation in LA HNSCC (118)(119)(120)(121)(122)(123).…”
Section: Targeting the Tumor Microenvironment Of Hpv +-Hnsccmentioning
confidence: 99%
“…Several studies have been performed with different strategies regarding the treatment of head and neck carcinoma. Whether combining drugs with radiation or just using immunotherapy, recent trials indicated positive results regarding not only the regression of the tumors, control of metastatic rates and recurrent behavior, but also severe adverse events (85). The trials looked at the effects of specific drugs such as HF-10, pembrolizumab, Lenvatinimib, cetuximab, vismodegib or survivin-2B peptide alone or in combination with radiotherapy.…”
Section: Downregulation Of Anti-apoptotic Proteinsmentioning
confidence: 99%